Simulação da dinâmica operacional de um processo industrial de abate de aves - Ebert, Douglas Cezar (2007)
Slaughter and meat processing of poultries occur at the environment called poultry slaughter industry where are carried out unitary operations logically organized. According to Operations Research fundaments a poultry slaughter industry is characterized as system which is associated the following factors: (i) input variables example: daily number of poultries to be slaughtered; and daily schedules; (ii) system parameters example: processing rates and water and vapor availabilities; and (iii) output variables example: production quantities of meats and derivatives, fixed and variable costs, and waist volumes. In reason of the number of factors involved, and the fact of theses could be stochastic, it is hard to define mental scenarios to support decision processes. In reason of that, use of simulation technique is appropriate, because it permit to realize experiments such as: sensitivity analysis, scenario analysis, optimization, and Monte Carlo simulation. Therefore, this work was carried out with objective to develop a computational model, using the simulation language EXTENDTM to (a) simulate the dynamic of poultry slaughter industry; and (b) realize sensitivity analysis. Developed model was classified as dynamic, stochastic and discrete. The real system modeled is located in Paraná State at Southwest Region and has daily slaughter capacity of 500,000 poultries, using three processing lines and operating in three daily schedules. At model validation was obtained data related to three schedules that were slaughtered 174,239; 166,870 and 144,021 poultries, respectively. Output variables contrasted, considering data obtained from system and generated by model, were: (i) processing time; (i) total live weight (kg); (iii) available live weight (kg); (iv) sub product weight (kg); (v) total production weight (kg); (vi) whole slaughtered poultry weight (kg); and (vii) total slaughtered poultry part weight (kg). Sensitivity analysis carried out, by changes lines processing rates in 7,000; 8,000 and 9,000 poultries per hour, showed the following averages for processing time 8.69, 7.86 and 7.86 hours, respectively. Results demonstrate that for current situation, the increase of processing rates in 9,000 poultries h-1 does not imply in a directly decrease of processing time, because current frequency of cargos arrives can establish idle periods of poultry slaughter facility.